Market participation and profitability of small scale garri processing in Edo, Ogun and Oyo States, Nigeria - Jelili Olaide Saka; Veronica Adeoti Obatolu; Bosede Olukemi Lawal; Ayodeji Babatunde Idowu; Chukwudi Peter Amadi; Johnson Adedayo Adetumbi; Taofik Oyedele Dauda (Journal of Agriculture and Rural Development in the Tropics and Subtropics)
Nigeria is the largest producer of cassava which is a staple food crop consumed in different forms. garri is one of the products commonly consumed by households. Improving the production process for greater gains has been at the fore front of discourse on potential for growth of the garri industry. Studies have not adequately explored variations in processing techniques across major producing and consuming communities for evaluation of the associated commercial potentials. This study examines market participation, cost structure and profitability of garri processing in major producing communities of Nigeria. Data were collected through survey of 300 processors selected by multi-stage sampling technique in Edo, Ogun and Oyo states of Nigeria. The results show that garri processing varies in length of processing period, quantity of cassava processed, garri yield and cost efficiency across the states. Processing was characterised by high market participation across the states while the cost structure shows that the bulk of the cost of garri processing was incurred on procurement of fresh tubers. A greater proportion of the labour cost was incurred on peeling (20.4%), washing (11.9%) and frying (31.1%). Garrification rates were higher in Ogun (26.54%, 20.25%) and Oyo (24.09%, 15.57%) than in Edo state (23.44%, 14.15%) in the dry and wet seasons respectively, with the latter having a shorter processing period. Cost per kilogram of garri produced was lowest in Edo state during the dry season but highest during the rainy season. However, garri processing was generally profitable, with significant differences in gross margin percentage (GM %) across states only in the rainy season. The highest GM% was recorded by processors in Ogun state (47.14%) followed by Edo (18.92%) and Oyo (17.37%) states. Market participation and profitability indicated potential for increased investment in cost- and labour-saving technologies to improve productivity in the garri processing industry.